2005
DOI: 10.1002/adem.200400219
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Mechanisms of Nanostructured Al Alloys

Abstract: Cryomilling has emerged in recent years as an effective approach to process large amounts of nanostructured Al alloys. In the present review, progress in our understanding of the microstructural characteristics and deformation behavior of nanostructured Al alloys processed via consolidation of cryomilled nanostructured powders is reviewed in an effort to elucidate salient findings and point out additional studies needed. A survey of published papers show that the microstructure of consolidated cryomilled Al al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 61 publications
2
25
1
Order By: Relevance
“…It has been suggested that such phenomena may involve GB sliding or grain rotation accompanied by shortrange diffusion-assisted healing events. [6] A review of these studies [1][2][3][4][6][7][8][9][10][11][12] shows that the data obtained by different investigators are not completely consistent. Various aspects characterizing these consistencies and limitations are identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that such phenomena may involve GB sliding or grain rotation accompanied by shortrange diffusion-assisted healing events. [6] A review of these studies [1][2][3][4][6][7][8][9][10][11][12] shows that the data obtained by different investigators are not completely consistent. Various aspects characterizing these consistencies and limitations are identified.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, creep and superplasticity, [1,2] cold rolling and annealing, [3] and the quantitative understanding of the mechanical behavior [4] of nanostructured materials have been the subject of a number of studies.…”
Section: Introductionmentioning
confidence: 99%
“…as a function of grain size, which has been reported in a number of studies. 11 In general, the amount of strengthening for grain sizes smaller than 50 nm makes nanocrystalline materials an attractive candidate system for future applications over its coarsegrained counterparts. Moreover, the ability to use solute segregation to grain boundaries, the introduction and dispersion of second phases, and the grains of secondary elements/phases can lead to even better mechanical properties.…”
Section: Introduction Mechanical Properties Of Nanocrystalline Materialsmentioning
confidence: 99%
“…The room temperature results also show a very weak strain hardening behavior, in contrast to the strain hardening observed for commercially available CG Al-5083 H131(This is demonstrated in [31]). This phenomenon is commonly observed with cryomilled UFG materials [1,32]. For UFG materials, the reduced size of the grain interior limits the amount of dislocation accumulation as mobile dislocations will often reach a grain boundary and annihilate before interacting with another dislocation.…”
Section: Resultsmentioning
confidence: 94%